MicroRNA profiling in aplastic anemia reveals similarities between secondary myelodysplastic syndromes arising from clonal progression and de novo MDS - Chee, Lynette; Koldej, Rachel; Thio, Niko; Ludford-Menting, Mandy; Fox, Lucy; Blombery, Piers; Ritchie, David (Frontiers in Hematology, 2023)
Aplastic anaemia (AA) is a form of bone marrow failure (BMF) resulting in significant cytopenias and may progress with clonal evolution to myelodysplastic syndromes (MDS) and acute myeloid leukaemia (AML). MicroRNA expression is dysregulated in MDS/AML but there are limited studies on its role in the pathogenesis of AA. Using stored BM samples (n=81) from 2006-2019 from 52 patients, we demonstrate key differences in miRNA expression between AA patients at diagnosis and de novo MDS patients (n=21). The five most significantly upregulated miRNA in MDS patients (downregulated in AA) were miR-130a-3p, miR-221-3p, miR-126-3p, miR-27b-3p and miR-196b-5p (adj p<0.001). However, at the time of AA clonal progression to secondary MDS/AML, no significant miRNA differences were identified suggesting that the underlying mechanistic pathways are similar between AA progression to MDS/AML and de novo MDS. At diagnosis, miR-127-3p, miR-1271-5p, miR-301b-5p, miR-3934-5p and miR-4531 (adj p=0.081) were upregulated in those whose AA eventually progressed in comparison to those without eventual clonal progression.Longitudinal molecular mutational analysis of myeloid genes in AA patients with disease progression revealed acquisition of new mutations mostly at time of MDS/AML progression with 4 patients developing mutations prior to morphological MDS progression. In contrast, no myeloid gene mutations were detected at diagnosis nor follow-up in AA patients with no clonal progression. Using KEGG pathway analysis derived from miRPathDBv2.0, cytokine-cytokine receptor interaction, TGF-b, MAP kinase, prolactin, Hippo, neurotrophin and FOXO signalling pathways were enriched in AA patients with clonal progression to MDS/AML; these pathways were similarly enriched in the de novo MDS cohort. These studies highlight the differing miRNA expression profiles in AA and MDS, in AA clonal evolution to MDS/AML and the potential interplay with myeloid gene mutations acquired at time of disease progression.